(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Purpose - The study aimed at evaluating the accounting system of the Iraqi political parties, which is applied according to legislative texts, and then the ability to provide accounting information to evaluate the strategic performance and control of the party’s operational and financial performance. Findings- The research found that the unified accounting system applied to political parties does not provide relevance informations to judge the performance of the political party, the researcher a proposal for an accounting system that provides the necessary information to measure and monitor the performance of Iraqi political parties can be presented. The Proposed Introduction to Activate the Role of Accounting System for Political Parties in Iraq